Metode Dakwah Dalam Menghadapi Perkembangan Budaya Populer - Istiqomalia, Yuntarti (STID Al-Hadid, 2022)
Popular culture has entered and influenced the realm of religion and da'wah. This is shown by the many programs on almost every TV station that carry da'wah broadcasts and have Islamic nuances. However, this method of da'wah with popular culture displays more aspects of mere entertainment and makes Islamic teachings conveyed superficially so that people like them and bring benefits to cultural industry players. Thus, da'wah is currently faced with the challenge of the rise of popular culture in society. This article wants to explain the method of preaching to the community in the midst of challenges from the influence of popular culture. The results are in the form of principles in choosing da'wah methods and forms of da'wah methods based on these principles. The concepts of da'wah, da'wah methods, and popular culture are the main things that will be synthesized using a qualitative non-empirical research approach. The principles in choosing the da'wah method in dealing with the development of popular culture are: aiming to popularize Islamic teachings, must contain adequate explanations and accountability, contain elements of entertainment in a reasonable manner, packaged in a simple and easy to understand manner, and delivered massively. Meanwhile, the form is in the form of oral, written, and action da'wah methods.